a 5 − a 4 − a 3 + a 2 a 3 + 1
Let a be one of the roots of the equation x 2 − x − 4 = 0 . The value of the expression above is a form of n m . Submit your answer as m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Very neat solution. Keep it up!
Can you explain the second line? You seem to be claiming that − a 2 + a = 0 .
While your solution seems to suggest that this problem is all about trickery, there is a very simple mathematical reasoning behind the approach. Do you see how one can approach this logically, without a lot of tricky trial and error?
Log in to reply
Sorry sir, the second line, where i mean − a 2 + a is a typo. It supposed to be − a 2 + a 2 . Thank you!
Since a is a root of x 2 − x − 4 = 0 , we have a 2 = a + 4 .
By repeatedly multiplying this equation by a , we may work out the powers of a , like so: a 3 = a ⋅ a 2 = a ⋅ ( a + 4 ) = a 2 + 4 a = ( a + 4 ) + 4 a = 5 a + 4 a 4 = a ⋅ a 3 = a ⋅ ( 5 a + 4 ) = 5 a 2 + 4 a = 5 ( a + 4 ) + 4 a = 9 a + 2 0 a 5 = a ⋅ a 4 = a ⋅ ( 9 a + 2 0 ) = 9 a 2 + 2 0 a = 9 ( a + 4 ) + 2 0 a = 2 9 a + 3 6
Using this, we may simplify the numerator and denominator: a 3 + 1 = ( 5 a + 4 ) + 1 = 5 a + 5 a 5 − a 4 − a 3 + a 2 = ( 2 9 a + 3 6 ) − ( 9 a + 2 0 ) − ( 5 a + 4 ) + ( a + 4 ) = 1 6 a + 1 6 , so that a 5 − a 4 − a 3 + a 2 a 3 + 1 = 1 6 a + 1 6 5 a + 5 = 1 6 5 where we note, as a sanity check, that a = − 1 , so the last step above is actually valid.
Problem Loading...
Note Loading...
Set Loading...
Since a is one of the roots of the equation x 2 − x − 4 = 0 , then, a 2 − a = 4 .
We can easily see that a 3 + 1 = a 3 − a 2 + a 2 + 1 .
We will do some tricky things. The expression a 3 − a 2 + a 2 + 1 can be written as a ( a 2 − a ) + a 2 + 1 = 4 a + a 2 + 1 .
Again, another tricky thing. 4 a + a 2 + 1 = ( a 2 − a ) + 5 a + 1 = 4 + 5 a + 1 .
Now, we have a 3 + 1 = 5 a + 5 = 5 ( a + 1 ) .
For the denominator, we simplify, a 5 − a 4 − a 3 + a 2 = a 3 ( a 2 − a ) − a ( a 2 − a ) .
Another tricky thing, 4 a 3 − 4 a = 4 a ( a 2 − 1 ) = 4 a ( a 2 − a + a − 1 )
Simplify, we have 4 a ( 4 + a − 1 ) = 4 a ( a + 3 ) = 4 a 2 + 1 2 a = 4 a 2 − 4 a + 1 6 a = 1 6 + 1 6 a .
So, we have a 5 − a 4 − a 3 + a 2 = 1 6 ( a + 1 ) .
Hence, we have a 5 − a 4 − a 3 + a 2 a 3 + 1 = 1 6 5 = n m .
m + n = 2 1